Social Adaptation of Persons released from Places of Deprivation of Freedom as Prevention of Recidivism - BALGOZHINA, Maigul Egeubaevna (Journal of Advanced Research in Law and Economics; Vol 6 No 2 (2015): JARLE Volume VI Issue 2(12) Summer 2015, 2016)
The article explores the problems of social adaptation of persons, released from places of deprivation of freedom, as a multidimensional factor in preventing recidivism. The points of view of different researchers, the statistics of committing repeated offences, the relevant rules of legal regulation, the legal experience of a number of foreign countries have been studied. It has been noted that the problem of recommitting crimes is closely allied to unemployment of ex-prisoners. The problems of luck of legal basis of cooperation between the penal enforcement system and the employment service, absence of generalized information about the situation in the field of social adaptation of ex-prisoners have been also shown. In author’s opinion, the activity of local rehabilitation centers for ex-prisoners, existing in some regions of Kazakhstan, new regional projects providing different types of social assistance, must be encouraged. Summarizing the information studied, the author supports the idea of drafting a basic law on social adaptation of ex-prisoners as a main legal measure.
Keywords: recidivism, social adaptation, resocialization and best practices